Measuring and modeling the solubility of sulfasalazine in supercritical carbon dioxide to select methods for producing nanoparticles - Yahia Alghazwani; Mohammed Ghazwani; Sirajunisa Talath; Adil Farooq Wali; Sathvik B. Sridhar; Farhat Fatima; Umme Hani (Scientific Reports)
Abstract In the present study, the solubility of sulfasalazine in carbon dioxide was investigated at temperatures ranging from 313 K to 343 K and pressures ranging from 12 to 30 MPa. The experimentally determined molar solubilities of sulfasalazine in ScCO2 were found to be in the range of 4.08 × 10− 5 to 8.61 × 10− 5 at 313 K, 3.54 × 10− 5 to 11.41 × 10− 5 at 323 K, 3.04 × 10− 5 to 13.64 × 10− 5 at 333 K, and 2.66 × 10− 5 to 16.35 × 10− 5 at 343 K. The solubility values were correlated via a number of different types of equations, such as semi-empirical correlations, the Peng-Robinson, the PC-SAFT equation, and the regular solution. Furthermore, the findings demonstrate that semi-empirical, equation of state models, and the regular solution model possess the capability of precisely determining the solubility. Moreover, the solubility magnitude suggests that the gas anti-solvent method may be a viable approach for nanoparticle production.